Author Correction: Phase-resolved X-ray polarimetry of the Crab pulsar with the AstroSat CZT Imager. (May 2018) - Vadawale, S.; Chattopadhyay, T.; Mithun, N.; Rao, A.; Bhattacharya, D.; Vibhute, A.; Bhalerao, V.; Dewangan, G.; Misra, R.; Paul, B.; Basu, A.; Joshi, B.; et al.
In the Supplementary Information file originally published for this Letter, in Supplementary Fig. 7 the error bars for the polarization fraction were provided as confidence intervals but instead should have been Bayesian credibility intervals. This has been corrected and does not alter the conclusions of the Letter in any way.